Advances in Intelligent Data Analysis XII 12th International Symposium, IDA 2013, London, UK, October 17-19, 2013, Proceedings - Tucker, Allan; Höppner, Frank; Siebes, Arno; Swift, Stephen (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2013)
This book constitutes the refereed conference proceedings of the 12th International Conference on Intelligent Data Analysis, which was held in October 2013 in London, UK. The 36 revised full papers together with 3 invited papers were carefully reviewed and selected from 84 submissions handling all kinds of modeling and analysis methods, irrespective of discipline. The papers cover all aspects of intelligent data analysis, including papers on intelligent support for modeling and analyzing data from complex, dynamical systems.